Investigation of Crack Depth on Reinforced Concrete Beam Using Vibration-Based Method - Tham Yee Mei; Nor Hayati Abd Ghafar (Journal of Structural Monitoring and Built Environment, 2024)
Basic types of damage to a concrete structure include cracks, which can lower the structure’s stiffness and load-bearing capacity as well as causing failures and tragedies in buildings under construction. As a result, it’s essential to keep an eye on the structural responses in order to assess the health of the buildings, guarantee their operational safety, and identify damage early on. Damage-related changes to the structures’ physical characteristics, such as their natural frequency and mode shape that might modify the dynamic response. These parameter changes can be extracted to predict damage detection information, such as the presence, location, and severity of damage in a structure. Thus, in this study, two non-destructive test methods ambient vibration test and impact hammer test were carried out to determine the vibration behaviour of cracked and uncracked of simply supported beams. Moreover, the position of various crack depth from 0mm to 150mm with 50mm interval were determined at the midspan of 0.60m x 0.25m x 0.25m reinforced concrete beams. The result showed, the natural frequency of cracked beam is lower than uncracked beam. Besides, propagation path of wave altered differently with various crack depth. The severity of cracks also can be determined by observing the curve fitting graph where the wave pattern propagate.